Early Functional and Structural Microvascular Changes in Hypertension Related to Aging - de Moraes, Roger; Tibirica, Eduardo (Current Hypertension Reviews, 2017)
It is becoming increasingly clear that both microvascular network alterations and subsequent tissue perfusion defects may precede and predict the development of arterial hypertension and other cardiovascular and metabolic diseases, including diabetes and metabolic syndrome. Moreover, the subsequent functional and structural alterations in microvascular reactivity and density, as well as alterations in the macrocirculation characteristic of physiologic vascular aging, contribute to the development of target organ damage. Microvascular rarefaction appears to be an early vascular structural alteration in the setting of hypertension, as it is already present in individuals presenting with borderline hypertension and normotensive young adults with a familial predisposition to high blood pressure. The chronic increases in blood pressure that occur during senescence secondary to macrocirculatory changes induce vasoconstriction within the microcirculation, which promotes the development of tissue hypoxia and reduces both arteriolar and capillary density. This phenomenon contributes to additional increases in peripheral vascular resistance and establishes a vicious cycle that culminates in both tissue injury and target organ damage, which are equally present in senescence and hypertension. Therefore, the microcirculation may be considered an essential target for both the pharmacological and non-pharmacological treatment of arterial hypertension and other cardiovascular diseases.
Keywords: Hypertension